2019
DOI: 10.1037/ccp0000417
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal profiles in emotional disorders predict the importance of alliance negotiation for early treatment outcome.

Abstract: The aim of this study was to identify differential baseline profiles of interpersonal problems in patients with emotional disorders and investigate their ability to predict the extent to which alliance is important for early treatment outcome in therapy. Method: Ninety-six patients diagnosed with emotional disorders were admitted to psychotherapy at an independent practice center. After the first session, participants completed the Inventory of Interpersonal Problems and, after each of the first four sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
0
12
0
3
Order By: Relevance
“…For instance, analyzing in-session rupture-repair episodes on the alliance also provided evidence of within-patient effects of alliance on outcome (Eubanks et al, 2018). Future studies might benefit from exploring how patients' interpersonal problems may have an effect on the association between alliance rupture-resolutions with outcome (Gómez Penedo, Zilcha-Mano, & Roussos, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, analyzing in-session rupture-repair episodes on the alliance also provided evidence of within-patient effects of alliance on outcome (Eubanks et al, 2018). Future studies might benefit from exploring how patients' interpersonal problems may have an effect on the association between alliance rupture-resolutions with outcome (Gómez Penedo, Zilcha-Mano, & Roussos, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these baseline predictors, the intrinsic relational nature of the alliance suggests patients’ interpersonal problems as promising candidates to moderate the effects of alliance on therapy outcome (Gómez Penedo, Zilcha-Mano, & Roussos, 2019). Patients with certain interpersonal difficulties might benefit substantially from an improved alliance, whereas for patients with other interpersonal issues such change may not be as decisive (Constantino, Coyne, et al, 2017).…”
mentioning
confidence: 99%
“…Empirically, scholars have begun to identify specific interpersonal profiles characterizing those with psychological disorders or personality disorders (Locke et al, 2018). In one study, two interpersonal problem profiles—cold interpersonal problems (too hostile) and overly nurturant interpersonal problems (too dependent)—were identified for patients with emotional disorders (Gómez Penedo et al, 2019). Taking both the interpersonal theoretical perspective and empirical evidence together, different interpersonal problem profiles might have differences in their levels of psychological outcomes.…”
Section: Studymentioning
confidence: 99%
“…Salzer et al (2011) described four interpersonal subtypes (Overly Nurturant, Intrusive, Socially Avoidant, and Nonassertive) for those with generalized anxiety disorder. Using cluster analysis and SSM, Gómez Penedo et al (2019) reported that cold interpersonal problems (too hostile) and overly nurturant interpersonal problems (too dependent) characterize patients with emotional disorders. Solomonov et al (2020) who used cluster analysis and SSM, reported that individuals with obsessive-compulsive personality disorder could be classified into two distinct interpersonal subgroups on opposite sides of the interpersonal problem circumplex: (a) “aggressive” (i.e., Vindictive-Domineering) and (b) “pleasing” (i.e., Submissive-Exploitable).…”
mentioning
confidence: 99%
“…Uno de los ejemplos más difundidos es el del Outcome Questionnaire (OQ-45;Lambert et al, 1996;Lara, Cruz, Vacarezza, Florenzano, & Trapp, 2008), cuyo uso en países como Chile y Argentina es frecuente (p. ej., Barros et al, 2020;Gómez-Penedo, Zilcha-Mano, & Roussos, 2019;Roussos, Gómez-Penedo, & Muiños, 2018;Zilcha-Mano & Errázuriz, 2015). Dicho cuestionario se presenta como una medida psicométricamente rigurosa, que abarca los motivos de consulta más comunes de las personas que solicitan psicoterapia, y que es sensible a modificaciones en períodos breves, lo que facilita su uso para monitorear procesos de cambio.…”
Section: Introductionunclassified